Jesus as the son of 1-2 Samuel's David: an intertextual reading of the Gospel of Matthew - Grønbech-Dam, Marc (Biblical interpretation series, 2024)
An intertextual reading of Matthew's Gospel, exploring how 1-2 Samuel influence Matthew's portrayal of Jesus as a new David. Matthew's Jesus both imitates and inverts the acts of King David in ways that promote righteousness and mercy.